PROGRAM IMPLEMENTATION AUTORIZED ECONOMIC OPERATOR (AEO) IN INDONESIA - Surono Surono; Benedictus Janrian Purba (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The national program of Authorized Economic Operators (AEO) program is a mandate that must be carried out by customs administrations in each country according to the agreement on WCO SAFE Framework of Standards, is adopted in 2005. Indonesia has expressed its commitment to implementing this program since the signing of the letter of intent of WCO SAFE FoS in 2005. The results of research analysis on the implementation of the AEO program in Indonesia show the conclusion that (1) the high interest of economic operator companies to participate in the AEO certification program is due to the potential benefit factor that will be received. Second (2), there are 13 standard conditions and requirements that must be met by AEO companies which are based on the DGCE Regulation number PER-4/BC/2015 breakdown into 51 criteria. This is a challenge that needs to be faced by enthusiasts of the AEO program to avoid administrative failure rates in the certification process. Finally (3), the efforts made by Customs in increasing the number of AEO certified companies, among others, by active socialization to economic operator companies and also Customs vertical units in the regions, carrying out Focus Group Discussions, and the most strategically developing a coaching clinic program as a form of assistance to economic operator companies who are interested in participating in the AEO program. Keywords: Authorized Economic Operator, AEO, WCO SAFE Framework of Standards